Effectiveness of Public Service Policy Implementation: Analysis of Service Quality Influence on Fish Farmers' Satisfaction with Trust Mediation at UPTD BBIAT Pekalongan - Fahrudin Fahrudin; Karmanis Karmanis; Charis Christiani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the effectiveness of public service policy implementation at the Regional Technical Implementation Unit of the Freshwater Fish Cultivation Center (UPTD BBIAT) in Pekalongan Regency, focusing on the influence of service quality on fish farmers' satisfaction mediated by trust. The research employs a mixed-methods approach with a concurrent embedded design, combining a survey of 40 fish farmers and in-depth interviews with 5 key informants from the UPTD and Agency levels, along with observation and document analysis. The theoretical framework is built on New Public Service Theory, Policy Implementation Theory, and the SERVQUAL, trust, and public satisfaction concepts. The research findings indicate that all three variables are in the high category with robust and significant positive correlations: service quality with trust, service quality with satisfaction, and trust with satisfaction. Trust has been shown to play a strong mediating role in the relationship between service quality and fish farmers' satisfaction. The assurance and empathy dimensions are the strengths of UPTD BBIAT, while tangibles and reliability require improvement through infrastructure modernization and enhanced consistency in seed availability. Theoretically, this research confirms the applicability of the SERVQUAL model and trust theory in the context of public services in the fisheries sector. In practice, it provides strategic recommendations to improve policy implementation effectiveness through infrastructure strengthening, human resource development, service digitalization, and enhanced institutional coordination.